Implementation of Marketing Mix as an Effort to Create Sustainable Tourism Management at Mount Fatuleu Tourist Attraction, Nunsaen Village, Kupang Regency - Agustino Lukas Fischer Conterius; Yosefus Conterius; Veronika A.S.M. Flora; Anselma L. R. Saputri (International Journal Labs, 2026)
The tourism sector in Indonesia offers significant potential for regional economic development, but many destinations face challenges in sustainable management and effective marketing. This study focuses on the Mount Fatuleu tourist attraction in Nunsaen Village, Kupang Regency, which has experienced a decline in visitors and environmental degradation after the COVID-19 pandemic and Tropical Cyclone Seroja in 2021. The study examines the implementation of the marketing mix as an effort to create sustainable tourism at Mount Fatuleu using the 7P approach. This descriptive research uses qualitative methods, collecting data through observation, in-depth interviews, documentation, and library research. Data analysis follows Miles and Huberman’s techniques: Data Reduction, Data Display, and Conclusion Drawing/Verification, supported by data triangulation for validity. The 7P marketing mix—product, price, place, promotion, human resources, physical evidence, and processes—has not been fully implemented simultaneously by Mount Fatuleu’s management. This incomplete implementation has led to degradation of both its tourism potential and its tourist attractions. Consequently, the concept of sustainable tourism has not been actualized at Mount Fatuleu, limiting its ability to recover and develop sustainably